Edukasi Low Back Pain Musculoskeletal Disorders pada Pegawai Kantor di PT Prima Bahari Sejahtera Kota Batam - Raymond Oskar; Safun Rahmanto (CV. SINAR HOWUHOWU, 2025)
Introduction: Low back pain is a common problem experienced by office workers. This condition is associated with sitting position, length of sitting time, position at work, and type of chair used. It can occur due to age, gender, and BMI. Objective: The purpose of this counselling is to educate about the management of low back pain. Methods: The method in this counselling is service learning (SL) to office employees at PT Prima Bahari Sejahtera. Results: Participants in this counselling were 40 employees at PT Prima Bahari Sejahtera, then there was difference chang of the before-after results from 9% to 89%. Conclusion: There is an increase in understanding of myogenic low back pain.